Fabrication induced spring-back in thermosetting woven composite parts with variable thickness. (February 2018) - Ali, Mumtaz; Nawab, Yasir; Saouab, Abdelghani; Anjum, Aima Sameen; Zeeshan, Muhammad
Rising demand of composite materials for high performance application require a process to manufacture composite parts with accuracy and precision. Residual stress and consequent deformation is one of major limitation in growth of composite industry. Experimental studies reported in literature focused on uniform thickness plates, L shape brackets or rings but depending upon its application, e.g. wind turbine blade, conical structures, etc., real parts do not have always the uniform thickness. In the present study, effect of increasing thickness of a part, variable thickness within a part, angle of bracket, gradient of resin content, and convex and concave tooling on the process induced deformation in angled brackets is studied experimentally. The deformation was divided into two segments: warpage and spring back angle, which were measured using spherometer and microscope along with Scope Image Plus software, respectively. Scanning electron microscopy was used to observe presence of resin content gradient. It is observed that behavior of parts having variation of thickness in them is quite different than the uniform thickness parts. Part having increased thickness at base and flange has up to 10% decrease in distortion. Increased thickness is only effective at larger angles, at sharper angles, there is increase in distortion when thickness is increased. Convex type of tooling induces lower spring-back as compared to concave one.